Application of IoT using nodeMCU ESP8266 on the Syringe Pump Device to Increase Patient Safety - Anjani, Annisa Gallela; Sunarto, Presillia Grisviani; Royan , Royan; Wibowo, Kusnanto Mukti; Romadhona, Gema; Sapundani, Rum; Mulyanto, Arif; Setiawan, Iwan; Jumrianto, Jumrianto; N. Prasath5, N. Prasath (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Nowadays, health care has turned out to be more technology-oriented. Today's technology is demanded to be practical and easy to use. Based on data, the number of uses of mobile devices based on the Android operating system has increased significantly. The open-source nature of android helps in programming applications easily according to user requirements. A syringe pump is a medical device that functions to enter the medicinal fluid into the patient's body at a certain dose and time automatically in mL/hour. The syringe pump is generally equipped with an alarm. Alarms have a vital function to provide information to nurses or doctors who are on duty. Medical officers cannot hear alarms if they are outside the patient monitoring room. This paper aims to design a syringe pump that is equipped with a NodeMCU8266 WiFi module to provide notifications via a smartphone so that nurses or doctors can know the alarm even though they are outside the patient monitoring room. So, this is expected can improve patient safety. In addition, this paper also aims to verify the size of the syringe against the drug flow rate. Based on the test results, the syringe pump can control the drug flow rate with a sensor accuracy of 0.0217 and an error rate of 0.6% at a target volume of 5mL. The syringe pump can also send alarm notifications to smartphones in real-time.